Perancangan Sistem Berbasis Pengetahuan Untuk Mendeteksi Kerusakan Notebook Menggunakan Web - Wilda Susanti, M.Kom; M. Hasmil Adiya; ST, M.A.B, Okto Fenta Riandi (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
There are many problems can happen to Hardware and Software notebook, those problems canbe detected from various symptoms, however in order to know exact problem types, it needs an expert onnotebook troubleshooting. Meanwhile there are small numbers of notebook troubleshooting experts,especially on remote areas. Therefore it needs a system that has ability of an expert on notebooktroubleshooting, whereby the system has notebook troubleshooting expertise about symptoms andproblems. This thesis designs an Expert System using Web-based application to help users in analyzingthe problem. The system uses Personal Home Page (PHP) as its web application language, and MyStructured Query Language (MySQL) as its Database Management System (DBMS). The benefits of theExpert System to detect notebook problems are easy-to-use and easy-to-access whereby users are ableto access the system using mobile phones that support Internet technology.Keywords: Expert System, Troubleshooting, Notebook, Database Management System.